Y=(x+1)2-7

Simple and best practice solution for Y=(x+1)2-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y=(x+1)2-7 equation:


Simplifying
Y = (x + 1) * 2 + -7

Reorder the terms:
Y = (1 + x) * 2 + -7

Reorder the terms for easier multiplication:
Y = 2(1 + x) + -7
Y = (1 * 2 + x * 2) + -7
Y = (2 + 2x) + -7

Reorder the terms:
Y = 2 + -7 + 2x

Combine like terms: 2 + -7 = -5
Y = -5 + 2x

Solving
Y = -5 + 2x

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Simplifying
Y = -5 + 2x

See similar equations:

| -y-8x=9y | | 20=2h+1 | | 3x-20=4x+8 | | (x+2+3j)*(x+2-3j)=0 | | t-24=15 | | F(x)=3x-2x+5 | | 12x+21=3(4c+6) | | 5x-(-1-2x)=8 | | 4x+5y=-16 | | 7(X^2+2)-X=-8X+55 | | -2(sin^2)x=3sinx+1 | | -5=4a+3 | | 4b-15=-3 | | 6+3(2r-2)-3(4r+4)-9= | | 50=10-t | | 57-p=42 | | 3y-3*6+2=0 | | 2y=8x-142 | | 11(n+5)=11 | | -7(5+5a)=210 | | x=26-12x-x^2 | | 6m-5=55 | | 4cos^2*2x=0 | | 66=6-10r | | 10-x=37 | | 3r-29=13 | | f(x)=26-12x-x^2 | | 4cos^22x=0 | | -5(4+y)= | | -pq-3pq= | | -8(2p)= | | 7=k+7+8k |

Equations solver categories